THE SURVEY OF STUDENTS INTEREST IN READING BOOK AT SMPN 1 AND SMPN 6 JAMBI CITY - Nuraini; Zurneli, Netty; Amalia, Shynta (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
This study aims to describe the reading interest of class VIII SMP Negeri in Jambi City. This research uses survey research method. Sampling in this study using cluster sampling technique. The number of samples in this study were 100 students from 2 well-known schools in Jambi City they are SMPN 1and SMPN 6 Jambi city. In this study, they were asked to fill out a questionnaire regarding students' reading interest as a research instrument. The data analysis technique used is descriptive analysis with quantitative data. The results showed that the reading interest of class VIII Junior High School in Jambi city was in the high category, namely 74.55%. This means that most students in the city of Jambi have a fairly high demand for reading, especially reading knowledge books.